Karakter Pendidikan Islam dan Problematikanya - Wahyudin (Sekolah Tinggi Ilmu Tarbiyah (STIT) Pemalang, 2014)
Today, especially in Indonesia, the education system implemented in schools is a form of systematic adoption of the Western education system. Is the development of creative and dynamic intellectual insights in various fields in the light and integrated in Islam, is a keyword that must accelerate the process, both on theoretical and practical grounds. Islamic education is education that is understood and developed from the teachings and fundamental values ​​contained in its basic sources, namely the Qur'an and Sunnah. Islamic education can also be understood as a process of civilizing and inheriting Islamic teachings, cultures and civilizations from generation to generation throughout its history. Islamic education is required to apply new approaches and orientations that are relevant to the demands of the age of principled and absolutism values ​​which are directed towards socio-cultural change trends. The problem that is often faced by the world of education, especially Islamic education, is the mixing of Western elements, ranging from educational institutions to the education system, for this it is necessary to intervene from Muslim communities to become agents of social change by encouraging creative and dynamic intellectual productivity in all fields of business integrated with Islam.